EFFORTS TO DEVELOP CHILDREN FINE MOTOR SKILLS THROUGH STICKING PICTURE PROPERLY BY USING COMBINATION OF EXPLICIT INSTRUCTION MODEL AND ASSIGNMENT MEDIA UTILIZING NATURAL MATERIALS - Fitriah, Rina; Degeng, I Nyoman; Widiati, Utami (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
Learning outcome in this increasingly competitive era of globalization demands the ability to think critically, creatively, communicate and collaborate and cooperation including a good social skill. The meaning of learning outcome is the changes that occur in the students, whether involving cognitive, affective, and psychomotor aspects as a result of learning activities. Cooperative Learning Model of Student Team Achievement Division (STAD) type emphasizes the activity and interaction among learners that enable cooperation and socialization among students and help each other in mastering the material to achieve a better learning outcome.